Performance Analysis and Trade Strategy Indonesia-MERCOSURE: Ministry of Trade, Ministry of Finance, IPB University (Jurnal Ekonomi dan Kebijakan Pembangunan, 2019)
Indonesia has established various cooperative relationships with Latin American countries. Various efforts to explore Indonesia's cooperation with other countries have been continuously done, especially with MERCOSUR founding countries (Brazil, Argentina, Paraguay, and Uruguay) as a potential market for Indonesian export products. The objectives of this study are (1) identifying the trade performance between Indonesia and MERCOSUR countries; (2) analyzing factors affecting Indonesia’s export to MERCOSUR countries; and (3) formulating strategies for trade cooperation between Indonesia and MERCOSUR countries. The analytical methods used are Qualitative Descriptive Analysis, Gravity Model, and SWOT Analysis.  The results show that the value of Indonesia's exports and imports to MERCOSUR countries is still small compared to other competing countries. Import tariffs imposed by MERCOSUR countries on Indonesia's main export products are still relatively high, on the contrary, import tariffs imposed by Indonesia on MERCOSUR's main products are relatively low. Indonesia's exports to MERCOSUR countries are positively and significantly affected by the GDP of MERCOSUR countries. The recommendations for Indonesia-MERCOSUR trade cooperation strategies are: (1) optimizing Indonesia's ability to meet the MERCOSUR market, especially for palm oil, rubber, auto parts, artificial fibers, footwear, coconuts, and tobacco; (2) increasing cooperation intensity in Free Trade Area (FTA) form; (3) improving tariff structure and non-tariff barriers; and (4) strengthening the economic diplomacy.